Neck Swelling in A Child: Now You See it, Now You Don’t? - Hakim, Ikram; See, Goh Bee; Abd Hamid, Hamzaini (IIUM Medical Journal Malaysia, 2020)
Jugular Ectasia is a rare benign swelling due to dilatation of jugular vein, which can occur in the internal, external or an anterior jugular vein. It is characterized by painless, soft, compressible unilateral swelling appeared on Valsalva maneuver. A 3-year-old boy presented with 2 months history of prominent mass over the right side of the neck on Valsalva maneuver is subjected to Doppler ultrasonography (USG) of the neck. Doppler Ultrasonography (USG) of the neck revealed prominent right jugular dilatation during Valsalva without any focal lesion with the normal caliber of the left internal jugular vein. Jugular ectasia should be included in the differentials of a benign neck swelling in children despite infrequently encountered. Dilated jugular vein on ultrasound Doppler on Valsalva maneuver is pathognomic of jugular ectasia. Early diagnosis with serial follow up can reduce parent’s anxiety and will reduce complications.